Health-Related Quality of Life in Sudanese Children with Nephrotic Syndrome: A Comparative Cross-Sectional Study - Naim FS; Bakhiet YM; Mohmmedahmed MA; Yousef BA (Dove Medical Press, 2024)
Fatima S Naim,1 Yassir M Bakhiet,2 Mohmmed A Mohmmedahmed,3 Bashir A Yousef4 1Department of Clinical Pharmacy, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 2Department of Pediatric Nephrology, Soba University Hospital, Khartoum, Sudan; 3Department of Pediatric Cardiology, Sudan Heart Centre, Khartoum, Sudan; 4Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Khartoum, SudanCorrespondence: Bashir A Yousef, Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Al-Qasr Ave, Khartoum, 11111, Sudan, Tel +249155662037, Fax +249183780696, Email bashiralsiddiq@gmail.comBackground: Nephrotic syndrome (NS) is an essential chronic disease in children that has a major impact on a child's health-related quality of life (HRQoL). This study aimed to evaluate the HRQoL of Sudanese children with NS and clinical parameters that can influence their HRQoL.Methods: This study was a descriptive cross-sectional of children with NS conducted in Khartoum state hospitals. A standardized PedsQLTM 4.0 Scale Score evaluated the HRQoL of the participants. Patients' socio-demographics, clinical data, and disease complications were collected using a data collection sheet. This study assessed the HRQoL of children with NS and compared it with apparent age and sex-matched to three groups (healthy children, children with chronic diseases, and kidney-transplanted children).Results: 80 children with NS were recruited from April to August 2021. Children over eight years old represented (63.8%) of the study subjects. The total mean HRQoL scores of nephrotic children were significantly lower than those of healthy children (78.46 ± 24.01) (p = 0.001) and those with other chronic diseases (78.45 ± 24.01) (p= 0.006); however, it was not significantly different from those with kidney transplantation. Socio-demographics did not significantly affect the total mean HRQoL scores of children with NS. Clinical parameters such as the duration of illness, "less than one year" (p= 0.006), and the minimum change nephropathy histopathology (p= 0.035) significantly lowered the total mean HRQoL scores of NS children. Regression analysis further confirmed that edema, proteinuria, and hospital admission had a high impact on the total mean HRQoL.Conclusion: The total mean HRQoL scores of children with NS were low and significantly lower than healthy children. Parameters such as the patient's socio-demographics and phenotype of NS had no significant effect on the total mean HRQoL scores of children with NS. However, other clinical parameters significantly lowered their total mean HRQoL scores.Keywords: health-related quality of life, nephrotic syndrome, clinical parameters, Sudanese children